O significado moral da compaixão: objeções e contra-objeções - Silveira, Peri Alexander da (2022)
Compassion is an emotion that responds to the suffering of others and motivates agents to help and/or provide some type of relief to those in situations that demand moral intervention. This suggests a fundamental moral aptitude. However, a significant group of philosophers have raised objections to its ability to reliably contribute to properly moral action. This study has as its fundamental objective to discuss the problem of the moral value of compassion. Starting with an analysis of the nature of this emotion, the main critiques of the moral character of compassion are discussed, and then the responses that can be made to these critiques are analyzed. In addition, part of the response to these criticisms is to demonstrate the relevance of compassion in applied ethics and bioethics. I seek to show, in a partial way, that despite what critics of compassion have claimed, there is room to argue that compassion has a central place in morality and that it preserves the necessary properties for moral motivation and action.